Comparison of reactive power control techniques for solar pv inverters to mitigate voltage rise in low-voltage grids - Almeida D.; Pasupuleti J.; Ekanayake J. (MDPI AG, 2023)
The greater integration of solar photovoltaic (PV) systems into low-voltage (LV) distribution networks has posed new challenges for the operation of power systems. The violation of voltage limits attributed to reverse power flow has been recognized as one of the significant consequences of high PV penetration. Thus, the reactive power control of PV inverters has emerged as a viable solution for localized voltage regulation. This paper presents a detailed study on a typical Malaysian LV distribution network to demonstrate the effectiveness of different reactive power control techniques in mitigating overvoltage issues due to high PV integration. The performance of four reactive power control techniques namely, fixed power factor control, scheduled power factor control, power factor control as a function of injected active power, and voltage-dependent reactive power control were analyzed and compared in terms of the number of customers with voltage violations, reactive power compensation, and network losses. Three-phase, time-series, high-resolution power-flow simulations were performed to investigate the potential overvoltage issues and to assess the performance of the adoption of reactive power controls in the network. The simulation results re-vealed that the incorporation of reactive power controls of solar PV inverters aids in successfully mitigating the overvoltage issues of typical Malaysian networks. In particular, the Volt-Var control outperformed the other control techniques by providing effective voltage regulation while requir-ing less reactive power compensation. Furthermore, the comparative analysis highlighted the sig-nificance of employing the most appropriate control technique for improved network performance. 2021 by the authors. Licensee MDPI, Basel, Switzerland.